Drebrin Autoantibodies in Patients with Seizures and Suspected Encephalitis. Issue 6 (10th April 2020) - Pitsch, Julika; Kamalizade, Delara; Braun, Anna; Kuehn, Julia C.; Gulakova, Polina E.; Rüber, Theodor; Lubec, Gert; Dietrich, Dirk; von Wrede, Randi; Helmstaedter, Christoph; Surges, Rainer; Elger, Christian E.; et al.
Abstract : Objective: Assess occurrence of the dendritic spine scaffolding protein Drebrin as a pathophysiologically relevant autoantibody target in patients with recurrent seizures and suspected encephalitis as leading symptoms. Methods: Sera of 4 patients with adult onset epilepsy and suspected encephalitis of unresolved etiology and equivalent results in autoantibody screening were subjected to epitope identification. We combined a wide array of approaches, ranging from immunoblotting, immunoprecipitation, mass spectrometry, subcellular binding pattern analyses in primary neuronal cultures, and immunohistochemistry in brains of wild‐type and Drebrin knockout mice to in vitro analyses of impaired synapse formation, morphology, and aberrant neuronal excitability by antibody exposure. Results: In the serum of a patient with adult onset epilepsy and suspected encephalitis, a strong signal at ∼70kDa was detected by immunoblotting, for which mass spectrometry revealed Drebrin as the putative antigen. Three other patients whose sera also showed strong immunoreactivity around 70kDa on Western blotting were also anti‐Drebrin‐positive. Seizures, memory impairment, and increased protein content in cerebrospinal fluid occurred in anti‐Drebrin‐seropositive patients. Alterations in cerebral magnetic resonance imaging comprised amygdalohippocampal T2‐signal increase and hippocampal sclerosis. Diagnostic biopsy revealed T‐lymphocytic encephalitis in an anti‐Drebrin‐seropositive patient. Exposure of primary hippocampal neurons to anti‐Drebrin autoantibodies resulted in aberrant synapse composition and Drebrin distribution as well as increased spike rates and the emergence of burst discharges reflecting network hyperexcitability. Interpretation: Anti‐Drebrin autoantibodies define a chronic syndrome of recurrent seizures and neuropsychiatric impairment as well as inflammation of limbic and occasionally cortical structures. Immunosuppressant therapies should be considered in this disorder. ANN NEUROL 2020;87:869–884